Direct current hysteresis loops of Fe-based amorphous ribbons under stress and torsion - Kamer, O; Birkok, G (Iop Publishing Ltd, 1999)
Iron-based amorphous ribbons with a positive magnetostriction constant have been investigated by means of the vibrating sample magnetometer technique. When the samples are subjected to torsion and tensile stress, their hysteresis loops exhibit distinct steps. The correlation between the shape of the loops and the stresses applied was explored both experimentally and by evoking a simple realistic model. In addition to the fundamental interest in the hysteresis phenomena in these materials, the observed good agreement has an immediate practical implication, in that it is more reliable to use direct current magnetization curves in the interpretation of neutron depolarization studies.